2017
DOI: 10.1097/jpa.0000000000000101
|View full text |Cite
|
Sign up to set email alerts
|

Revolution or Evolution? A Proposal for the Integration of Point-of-Care Ultrasound Into Physician Assistant Clinical Practice

Abstract: Advances in technology and increased affordability of machines have allowed ultrasound to become ubiquitous across the spectrum of medical care. Increasing portability has brought ultrasound to the point of care in multiple medical specialties. Formal ultrasound training is rapidly being incorporated into multispecialty residency programs and undergraduate medical education curricula, yet little formal training exists for physician assistants (PAs) on this emerging clinical adjunct. This article outlines recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…US can be applied in a traditional fashion, for examination of the abdomen by gastroenterologists and surgeons [10][11][12][13][14], the pelvis by gynaecologists [15,16], the heart by cardiologists [17], the mediastinum and lung by pneumologists, and other anatomical regions examined by their respective specialists. The role of radiology depends on historical issues and traditions [18][19][20][21]. The performance of ultrasound by clinicians can be a rewarding and satisfying part of their practice, enabling the rapid delivery of a powerful diagnostic and therapeutic tool.…”
Section: The Advantages Of Ultrasoundmentioning
confidence: 99%
“…US can be applied in a traditional fashion, for examination of the abdomen by gastroenterologists and surgeons [10][11][12][13][14], the pelvis by gynaecologists [15,16], the heart by cardiologists [17], the mediastinum and lung by pneumologists, and other anatomical regions examined by their respective specialists. The role of radiology depends on historical issues and traditions [18][19][20][21]. The performance of ultrasound by clinicians can be a rewarding and satisfying part of their practice, enabling the rapid delivery of a powerful diagnostic and therapeutic tool.…”
Section: The Advantages Of Ultrasoundmentioning
confidence: 99%
“…Recently, we have started to address some of the above mentioned issues and developed two semi-automated methods to delineate and track displacements of the IVC borders in long (4,8,23,24) or short axis views (12). Our approaches could reduce the inter/intra-operator variability (8), assist in the interpretation of findings clinicians or sonographers with limited training and experience (25), and perhaps facilitate the diffusion of point-of-care US to guide clinical decisions. Our preliminary results suggest that the integration of indexes extracted by both algorithms could provide a more reliable estimation of the volemic status than using the standard IVC assessment (26) and call for extensions of research to larger databases and other vessels, like the arteries, the evaluation of which might improve cardiovascular risk stratification (27).…”
Section: Introductionmentioning
confidence: 99%
“…11 Although emergency and critical care medicine societies advise that POCUS proficiency requires sufficient residency or fellowship training that includes quality assessment teaching sessions and at least 150 US scans covering a range of organs, clinically, POCUS is being widely adopted to guide clinical decisions by a variety of clinicians with relatively limited US skills and training. 12,13 Measurement of the collapsibility of the inferior vena cava (cIVC) predicts fluid responsiveness reasonably well when performed by expert sonologists in spontaneously breathing patients (area under the receiver operating characteristic curve [AUROC], 0.82). 14 However, work by our group showed that the test characteristics were not as favorable when POCUS examinations were performed by novice sonologists (AUROC, 0.69).…”
mentioning
confidence: 99%
“…Point‐of‐care US–guided IV fluid resuscitation offers the advantage of the near omnipresence of US machines in clinical environments and physician familiarity, which other noninvasive technologies such as bioreactance lack 11 . Although emergency and critical care medicine societies advise that POCUS proficiency requires sufficient residency or fellowship training that includes quality assessment teaching sessions and at least 150 US scans covering a range of organs, clinically, POCUS is being widely adopted to guide clinical decisions by a variety of clinicians with relatively limited US skills and training 12,13 …”
mentioning
confidence: 99%